Virtual Reality-Based Communication Media For Acrophobia Therapy - Widyo Nugroho; Abiyyu Zharif Nugroho; Septian Ade Nugroho (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
The rapid development of information and communication technology has a significant impact on the use of media to help patients in reducing anxiety. This study aims at developing virtual reality-based therapeutic media to overcome acrophobia. Model ADDIE is applied in this research. The results show the therapy system that utilizes the technology of virtual reality proven effective to treat acrophobics by bringing together people with acrophobia along with a direct object using desensitization and virtual reality assisted with 3D glasses as display media. In this invention, a virtual reality system for acrophobia therapy is developed by using the android operating system which characterized by a minimum android KitKat 4.4 specification. Keywords: Virtual Reality, Communication Media, Acrophobia Therapy